Empiric antibiotic therapy in urinary tract infection in patients with risk factors for antibiotic resistance in a German emergency department - Bischoff, Sebastian; Walter, Thomas; Gerigk, Marlis; Ebert, Matthias; Vogelmann, Roger (BMC infectious diseases, 2018)
The aim of this study was to identify clinical risk factors for antimicrobial resistances and multidrug resistance (MDR) in urinary tract infections (UTI) in an emergency department in order to improve empirical therapy.
Gesehen am 03.04.2018